Viscometric investigations and molecular interactions of some derivatives of 5-substituted indole dihydropyrimidines in mixed organic solvents - Heda, L. C.; Sharma, Rashmi; Mosalpuri, Sonraj R.; Chaudhari, Pramod B. (Eclética Química, 2010)
Colloid chemical behavior of indole dihydropyrimidines in non-aqueous solvent mixture benzene-methanol of varying composition has been investigated by viscometric measurements at 303K± 0.1. The viscosity of the system increases with the increase in concentration. The Trend Change Point (TCP) values have been determined by intersection of two straight lines, which are found to be dependent on the composition of solvent mixtures. The study confirms that the nature of synthesized compounds agglomerate formed below and above 50% benzene concentration is quite different. The viscometric data have been analyzed in terms of Einstein, Vand, Moulik and Jones-Dole equations. These well known equations have been successfully applied to explain the results of viscosity measurements and the viscometric parameters show that the behavior of compound changes in the proximity of 50% benzene concentration.